“Methodological Basis of Teaching Pen Drawing” - Adhamova Oltinoy Rafiqjon qizi (Genius Journals, 2023)
This article describes the methodical recommendations necessary for mastering the theoretical and practical skills of pencil drawing, with broad comments on the subject of pencil drawing taught to students of the field of fine arts of higher educational institutions.
Keywords: pencil drawing; fine art; young generation; company